Fair deal chocolate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Maya Gold chocolate, named after the Belize Indian farmers who harvest it, is being sold at some retail outlets in the UK. It is a product which carries the Fairtrade Mark, signifying approval by Oxfam, Christian Aid, Cafod and the World...